The Economic Theories of John Craig, A Forgotten English Economist - Bruce, Thor W. (Quarterly Journal of Economics, 1938)
Journal Article The Economic Theories of John Craig, a Forgotten English Economist Get access Thor W. Bruce Thor W. Bruce St. Louis University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 52, Issue 4, August 1938, Pages 697–707, https://doi.org/10.2307/1885040 Published: 01 August 1938